Forex Trading for Beginner With Using Simple Moving Average as Main Indicator and Bollinger Bands as Support and Resistance in GBP/USD TF H1 Period July 2012 - December 2012 - Sjahbunan, Adam Ultra; Surya, Budhi Arta (Journal of Business and Management, 2013)
Main goal of this thesis is, how to make the beginner trader can achieve a profit quickly and easily while investing in forex, just using basic technical analysis published by master forex on the internet namely is Kang_Gun or familiarly called KG_Forex and without using a broker. In this paper the author will use the basic theory published by KG_forex there are 4 types of Simple Moving Average as the main indicator and Bollinger Bands as a line of support or resistance. SMA 24 is useful to look at the price movement in the past period of 1 day, SMA 120 is useful to see movement in a past period of 1week, SMA 480 is useful to look at the price movement in a past period of 1 month and SMA 4 is useful to look at the price movement in past 4 hours . A cross between SMA 24 and SMA 4 and when prices have bounced back from the upper / lower Bollinger Bands. This is would be a signal for the beginning trader to perform open position. This basic method is compared with a more advanced method. This comparative method using 5 different types of Linear Weighted Moving Average as the main indicator and uses two types of Bollinger Bands as a line of support / resistance. After doing all the calculation in GBP / USD TF H1. Apparently comparative method will provide more profit than the first method. However the comparison method will give more ambiguous signal to the beginner traders. The results obtained by the first method is very adequate for beginner traders. When you do all these things in the first method with discipline they can get up to 11400 USD profit. For traders who are pretty experienced the authors suggest to propagate the information by increasing the number of indicators used and do not forget to always look for fundamental information. This thesis only focus only on GBP/USD in TF H1 using forex trading software namely Meta Trader 4. In period July 2012 – Desember 2012. The outcome of this thesis the beginner trader can investing in forex future trading without using broker and they can get enough profit at he beginning. This research can prove the efficiency of KG basic method and its easy to use it. Keywords: forex, SMA, BB, LWMA, KG_forex, investing, trading, derivative, Category:Finance; derivative, forex